Nutrient removal by rice–wheat cropping system as influenced by crop establishment techniques and fertilization options in conjunction with microbial inoculation - Amit Anil Shahane (Nature Portfolio, 2020)
Abstract Nutrient uptake by the rice–wheat cropping system (RWCS) is an important indicator of soil fertility and plant nutrient status. The hypothesis of this investigation was that the rate and sources of nutrient application can differentially influence nutrient removal and soil nutrient status in different crop establishment techniques (CETs). Cropping system yield was on par in all the CETs evaluated, however, there were significant changes in soil nutrient availability and microbiological aspects. The system nitrogen (N), phosphorus (P), potassium (K) and zinc (Zn) uptake in aerobic rice system followed by zero tillage wheat (ARS-ZTW) was 15.7–17.6 kg ha−1, 0.7–0.9 kg ha−1, 7–9.8 kg ha−1 and 13.5–23.1 g ha−1 and higher than other CETs. The formulations of Anabaena sp. (CR1) + Providencia sp. (PR3) consortium (MC1) and Anabaena–Pseudomonas biofilm (MC2) recorded significantly higher values of soil chlorophyll and microbial biomass carbon and positively affected cropping system nutrient uptake and soil nutrient balance, illustrating the beneficial effect of microbial inoculation through increased supply of biologically fixed N and solubilised P. Zinc fertilization (5 kg Zn ha−1 through ZnSO4·7H2O as soil application) increased soil DTPA-extractable Zn by 4.025–4.836 g ha–1, with enhancement to the tune of 20–24% after two cropping cycles of RWCS. Our investigation recommends the need for change in the present CETs to ARS–ZTW, along with the use of microbial inoculation as a means of significantly enhancing cropping system nutrient uptake and soil nutrient status improvement.